Analysis and Visualization of Incoming and Outgoing Mail Information System Based on Responsive Design - Tri Basuki, Kurniawan; Aditya, Umyanto (INTI International University, 2023)
The proliferation of information technology has made all aspects of human existence dependent on technical advancements. This includes the Jakabaring Subdistrict of Palembang, the place where we conduct our study. The incompetent management of the archive storage facility for incoming and outgoing mail is the issue facing the Palembang City Jakabaring Sub-district Office. After doing a thorough analysis, we conclude that there's no mechanism in place to handle the incoming and outgoing mail archives. Therefore, to help officers in the Jakabaring Subdistrict of Palembang generate reports more successfully, we offer a solution in the form of an application that visualizes incoming and outgoing mail data. The traditional Waterfall approach is the foundation of our solution. Requirement analysis, system design, WAR server, and system testing are the techniques used to implement the solutions. The study's findings suggest that officers may find it simpler to handle incoming and outgoing mail archives if they use a web-based application system